Sensitivity of Oncogenic KRAS-Expressing Cells to CDK9 Inhibition. (August 2021) - Lai, Lick Pui; Brel, Viviane; Sharma, Kanika; Frappier, Julia; Le-Henanf, Nadia; Vivet, Bertrand; Muzet, Nicolas; Schell, Emilie; Morales, Renaud; Rooney, Eamonn; Basse, Nicolas; Yi, Ming; et al.
Oncogenic forms of KRAS proteins are known to be drivers of pancreatic, colorectal, and lung cancers. The goal of this study is to identify chemical leads that inhibit oncogenic KRAS signaling. We first developed an isogenic panel of mouse embryonic fibroblast (MEF) cell lines that carry wild-type RAS, oncogenic KRAS, and oncogenic BRAF. We validated these cell lines by screening against a tool compound library of 1402 annotated inhibitors in an adenosine triphosphate (ATP)-based cell viability assay. Subsequently, this MEF panel was used to conduct a high-throughput phenotypic screen in a cell viability assay with a proprietary compound library. All 126 compounds that exhibited a selective activity against mutant KRAS were selected and prioritized based on their activities in secondary assays. Finally, five chemical clusters were chosen. They had specific activity against SW620 and LS513 over Colo320 colorectal cancer cell lines. In addition, they had no effects on BRAF V600E, MEK1, extracellular signal-regulated kinase 2 (ERK2), phosphoinositide 3-kinase alpha (PI3Kα), AKT1, or mammalian target of rapamycin (mTOR) as tested in in vitro enzymatic activity assays. Biophysical assays demonstrated that these compounds did not bind directly to KRAS. We further identified the mechanism of action and showed that three of them have CDK9 inhibitory activity. In conclusion, we have developed and validated an isogenic MEF panel that was used successfully to identify RAS oncogenic or wild-type allele-specific vulnerabilities. Furthermore, we identified sensitivity of oncogenic KRAS-expressing cells to CDK9 inhibitors, which warrants future studies of treating KRAS-driven cancers with CDK9 inhibitors.